Characteristics of Vertisols at ILCA research and outreach sites in Ethiopia - Kamara, C.S.; Haque, I. (International Livestock Centre for Africa, 1987)
A study of a soil profile conducted to investigate the characteristics of vertisols at the 10 ILCA research sites in Ethiopia. Describes the study sites with regard to activity climate and parent material. Presents the pedon description, physical and chemical analysis of each soil as well as the nutrient status and soil moisture storage for all the soils. Examines buried vertisols and indicates the causes.